EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN AUDIO-VISUAL TERHADAP PENINGKATAN PEMAHAMAN MATERI SHALAT SISWA KELAS IV SD NEGERI 74 PALEMBANG - Jami’atul Husna; Sujinal Arifin; Asri Karolina (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of the use of audio-visual learning media in improving the understanding of prayer material for fourth-grade students at SD Negeri 74 Palembang. The type of research used is quantitative research with a Quasi-Experimental design of One Group Pretest–Posttest Design. The research subjects consisted of 30 fourth-grade students selected using a total sampling technique. Data were collected through learning outcome tests (pretest and posttest), questionnaires, and observations of student learning activities. The results showed that the use of audio-visual learning media had a significant effect on improving student understanding. The average value of learning outcomes increased from 58.4 in the pretest to 83.1 in the posttest, with the results of the paired t-test showing a significance value of 0.000 < 0.05. This indicates that audio-visual media is effective in helping students understand the procedures, readings, and meaning of prayer. In addition, students became more active, enthusiastic, and able to practice prayer movements correctly. Thus, it can be concluded that audio-visual learning media is an effective, engaging, and relevant learning strategy for improving elementary school students' understanding of prayer, particularly at SD Negeri 74 Palembang.